KONTEKSTUALISASI INJIL DALAM KEHIDUPAN SOSIAL DAN RELIGIUS ORANG TORAJA - Grescia Pabuke; Megirianto; Ayu Emmanuella Rawe; Erfin Rombe Bala; Irene Sovia Rattin (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
This article examines the process of contextualizing the Gospel in the social and religious life of the Torajan people, which is an encounter between Christian teachings and local cultural values. Since the arrival of the Gospel by Dutch missionaries in the early 20th century, Torajan society has undergone significant spiritual and social transformation. Through a contextual approach, cultural values such as siri' (self-esteem), karapasan (harmony), respect for ancestors, and traditional social structures are reinterpreted in light of Christ's teachings. The local church, particularly the Torajan Church, plays a crucial role in accompanying this transformation process by not rejecting culture completely, but rather purifying it in accordance with Gospel values. This article also examines the church's struggles in responding to traditional practices such as rambu solo' and rambu tuka', as well as its efforts to become an agent of social transformation through education, health services, and economic empowerment. On the other hand, the challenges of globalization require the church to maintain its local faith identity amidst the currents of modernization and the pressures of global cultural homogenization. This research uses a descriptive qualitative approach with literature study, observation, and interview methods, as well as contextual hermeneutic analysis. The research findings show that contextualization of the Gospel is not merely a matter of liturgical adaptation, but also a reflective and transformational process that has a broad impact on community life. Thus, contextual Christianity in Toraja serves as a model of faith that is alive, grounded, and remains faithful to the truth of the Gospel.